CREATING BEST PRACTICES OF COMMUNICATION MANAGEMENT TO DRIVE THE MUNICIPALITY TOWARDS THE DIGITAL ORGANIZATION - Pariyasiri, Angkana; Tokeaw, Wittayatorn; Intaratat, Kamolrat; Princhankol, Pornpapatsorn (Journal of MCU Nakhondhat, 2025)
This research aimed to study 1) The development of best practices in communicating concepts and policies to drive municipalities toward digital organizations; 2) Best practices in communication planning to promote digital transformation within municipalities; 3) Best practices in communication implementation for advancing municipalities toward digital organizations; and 4) Best practices in evaluating communication effectiveness in the municipal digital transformation process. This study employed a mixed-methods approach. 1) Quantitative data were collected through questionnaires from two sample groups, Group 1 consisted of 850 municipal personnel from Maehia Town Municipality (Chiang Mai Province), Takli Town Municipality (Nakhon Sawan Province), Phichit Town Municipality (Phichit Province), and Phibun Mangsahan Town Municipality (Ubon Ratchathani Province), with a sample size of 265 respondents, Group 2 consisted of 73,138 citizens from the same municipalities. 2) Qualitative data was obtained through in-depth interviews with 40 key informants, including municipal executives and digital municipal task forces, conducted between March 2024 and March 2025. The research findings revealed that 1) Best practices in communicating concepts and policies involved a systematic flow of communication from organizational leaders to staff and citizens, emphasizing top-down, cross-functional, and citizen-to-government communication; 2) Best practices in communication planning involved clearly defined goals and strategies to enhance awareness, adjust attitudes, and promote the adoption of digital technology among personnel and citizens; 3) Best practices in communication implementation utilized diverse media channels, community activities, and the design of accessible, easily understood content; and 4) best practices in communication evaluation included the measurement of knowledge, attitudes, behaviors, and satisfaction levels among both personnel and citizens.